2014
DOI: 10.5121/ijics.2014.4201
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Three-Elements Boiler Drum Level Control and Its Installation in Power Plant

Abstract: Conversion of water into steam is the primary function of a utility boiler. The steam pressure is used to turn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…It inspired the idea of creating a similar system for the water-level control system. Such a control system has been studied for many years, as presented in Alouani et al 1 and Chakraborty et al 4 The studies focused on optimization and modernization of the control algorithm structure. In these systems, there were often unused diagnostic measurement circuits or expensive and not always effective instances of hardware redundancy.…”
Section: Conclusion -Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It inspired the idea of creating a similar system for the water-level control system. Such a control system has been studied for many years, as presented in Alouani et al 1 and Chakraborty et al 4 The studies focused on optimization and modernization of the control algorithm structure. In these systems, there were often unused diagnostic measurement circuits or expensive and not always effective instances of hardware redundancy.…”
Section: Conclusion -Discussionmentioning
confidence: 99%
“…Control system faults are among the most common causes of industrial process faults. They are presented in papers 4,[14][15][16]19,21 for industrial facilities' control systems. The solution described in this article analyses a special case whose application improves reliability of a power unit operation, which is of high importance when attempting to achieve more efficient power generation.…”
Section: Conclusion -Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gulhane and Thakur [5]find out amount and source of irreversibility's generated in boiler of 35 TPH boiler in 6 MW captive power plant.Kumar and Reddy [6]investigated on boiler to extract maximum amount of heat from the flue gases and increase the heat pick up rate of the feed water outlet into the boiler by incorporating the additional bank of tubes in the space below the lower bank of tubes.Costa et al [7]reported data on local mean gas species concentrations of O 2, CO, CO 2 , NO X , and gas temperatures measured at several ports in the boiler and burner region and incident wall heat fluxes taken around the boiler periphery at 39 ports.Kapooria et al [8]dealt steam cycles used in power plants, Enhancement of efficiency and reliability of steam power plants are studied.Jou et al [9]said the practical benefits for reducing energy consumption and greenhouse gas emission to the use of waste hydrogen rich refinery gas (RG) to partially replace the natural gas (NG). Chakraborty et al [10] discussed design aspects and installation requirements of boiler drum level control for safe and economic operation of thermal power plants.…”
Section: Introductionmentioning
confidence: 99%